A patent review of pharmaceutical and therapeutic applications of oxadiazole derivatives for the treatment of chronic diseases (2013–2021). (2nd September 2022) - Hassan, Abbas; Khan, Abid Hussain; Saleem, Faiza; Ahmad, Haseen; Khan, Khalid Mohammed
ABSTRACT: Introduction: Oxadiazole is a unique class of heterocycle, possessing numerous important biomedical and therapeutic applications, such as anti-bacterial, anti-cancer, anti-inflammatory, inhibitors for diverse enzymes, receptor modulators, and neuroprotective properties. The rapid development in the field of oxadiazole-containing structures is confirmed by the development of numerous clinical drugs, such as doxazosin, nesapidil, pleconaril, fasiplon, ataluren, zibotentan, and prenoxdiazine as selected examples. Areas covered: This review provides a comprehensive overview of the range of biological applications of oxadiazole-containing drugs in a range of patents from 2013 to 2021. The information was collected from available data sources including SciFinder, Reaxys, MedLine, and Chemical Abstracts. Expert opinion: Oxadiazole is an established class of compounds with fascinating biological properties. The importance of oxadiazoles can be recognized by their enormous application in a wide spectrum of medicinal chemistry from anticancer, lantibiotics, and antidiabetics to their use in agriculture and neuroprotection. For instance, the oxadiazole-based compounds have shown the ability to modulate a variety of receptors including the M4 receptor agonists, S1P1 receptor modulators, SSTR5 antagonists, orexin type-2 receptor agonists, liver X receptor agonists, and many more. This testifies to the special features associated with the oxadiazole scaffold, making it a significant pharmacophore.